Association between serum polybrominated diphenyl ethers, new flame retardants and thyroid hormone levels for school students near a petrochemical complex, South China. (July 2018) - Guo, Ling-Chuan; Xiao, Jianpeng; Zhang, Yonghui; Yu, Shengbing; Lin, Hualiang; Su, Guangning; Liu, Tao; Li, Xing; Lv, Shaomin; Rutherford, Shannon; Ma, Wenjun
Abstract: As surrogates of polybrominated diphenyl ethers (PBDEs), new flame retardants (NFRs) include a series of chlorinated and brominated flame retardants. Though the NFRs are thought to induce similar thyroid hormone (TH) disrupting effects as PBDEs, few studies have focused on them. Given the increasing levels of NFRs in the environment, more in depth investigation of the potential TH disrupting effects of NFRs is warranted. This research involved a health survey to collect data and examine the associations between PBDEs, NFRs and TH. 174 school students lived near a petrochemical complex in South China participated in the survey, completing questionnaires and providing blood samples. Thirteen congeners of PBDEs, eight species of NFRs, TH and thyroid-stimulating hormone (TSH) were measured. The median levels of ΣPBDE (sum of thirteen congeners of PBDEs) and ΣNFR (sum of eight species of NFRs) for students were 140 and 240 ng g −1 lipid, respectively. Nonmonotonic relationships were observed between quartile levels of PBDEs, NFRs and corresponding TH. In contrast to ΣPBDE that was positively associated with triidothyrine (T3 ) level, ΣNFR was not statistically associated with TH. ΣPBDE + NFR (sum of thirteen congeners of PBDEs and eight species of NFRs) was significantly associated with T3 level. Graphical abstract: Image 1 Highlights: Greater levels occurred for ΣNFR than for ΣPBDE in the serum of study students. Nonmonotonic relationships occurred between quartile levels of PBDEs, NFRs and TH. Influenced by BDE-209, ΣPBDE and ΣPBDE + NFR were positively associated with T3.